(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the effectiveness of 30% glycolic acid peel and triple combination cream (Hydroquinone, Tretinoin and Topical Steroids) versus triple combination cream in the treatment/therapy of epidermalmelasma. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Dermatology Unit Lady Reading Hospital Peshawar from March 2016 to September 2016. Materials and Methods: Total 178 patients having epidermal melasma were allocated at random into two equivalent groups by lottery process. Melasma was diagnosed with woods lamp examination and clinically and also having MASI score >12.Group A patients were treated with to 30% glycolic acid peel and triple combination cream. Group B Patients were treated with triple combination cream alone. Results were assessed after 4 weeks by calculating the MASI score. Chi square test of statistics was employed to compare the efficacy in two groups and p-value < 0.05 was considered for significance of parameters. Results: Group A had 20 (22.47%) male and 69 (77.53%) female patients. On the other hand, group B had 15 (16.85%) males and 74 (83.15%) female patients. Group A had 34(38.32%) patients of <26 years, 47(52.81%) of 26-40 years and 8(8.98%) above 40 years. Group B had 23(25.85%) patients of less than 26 years,53(53.56%) of 26-40 years and 13(14.61%) above 40 years. In group A, 84(94.38%) patients and in group B 71(79.77%) patients showed significant improvement. Conclusion: This study shows that treatment with 30% Glycolic acid peel and Triple combination cream is more efficient than triple combination cream therapy alone.